2020
DOI: 10.1111/vco.12658
|View full text |Cite
|
Sign up to set email alerts
|

Canine lymphoma and vector‐borne diseases: Molecular and serological evaluation of a possible complicity

Abstract: Lymphoma is the most common haematological malignancy in dogs and its aetiology is largely unknown. The presence of canine vector‐borne agents (CVBD) in lymphoma tissues has been described and its causative effects questioned. We intended to evaluate the presence and extent of Leishmania infantum, Ehrlichia canis, Anaplasma phagocytophilum and Bartonella henselae infection in dogs with lymphoma. Sixty‐one dogs, living in the Lisbon metropolitan area, with a diagnosis of lymphoma were enrolled. Immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Also interesting is the relationship reported between Leishmania and tumors, and immunohistochemistry can be a very useful technique. In addition to the possibility of mimicking tumors, as previously described [ 14 ], Leishmania has been detected in tumor cells of certain neoplasms, both in the dog [ 16 , 54 , 55 ] and in humans [ 10 , 13 ]. However, a causal relationship has not yet been demonstrated [ 54 ], although it suggests the ability of Leishmania to spread and infect different types of cells [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Also interesting is the relationship reported between Leishmania and tumors, and immunohistochemistry can be a very useful technique. In addition to the possibility of mimicking tumors, as previously described [ 14 ], Leishmania has been detected in tumor cells of certain neoplasms, both in the dog [ 16 , 54 , 55 ] and in humans [ 10 , 13 ]. However, a causal relationship has not yet been demonstrated [ 54 ], although it suggests the ability of Leishmania to spread and infect different types of cells [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the possibility of mimicking tumors, as previously described [ 14 ], Leishmania has been detected in tumor cells of certain neoplasms, both in the dog [ 16 , 54 , 55 ] and in humans [ 10 , 13 ]. However, a causal relationship has not yet been demonstrated [ 54 ], although it suggests the ability of Leishmania to spread and infect different types of cells [ 16 ]. It has been suggested that, in endemic areas, tumors should be a differential diagnosis and their possible association is worth investigating.…”
Section: Discussionmentioning
confidence: 93%
“…Although it is not clear how chronic inflammation can induce lymphoid proliferation, chronic inflammation has been associated with lymphoma and hemophagocytic syndromes. 1,7,9,16 This association has been documented in both canine and human patients who had lymphoma associated with Ehrlichia , Leishmania , and Borrelia spp. infections.…”
mentioning
confidence: 95%
“…14 HLH may occur independent of, or as a part of, a neoplastic process. 7 A 3-y-old, intact female, American Pit Bull Terrier was presented to the Tuskegee University Veterinary Medical Teaching Hospital (TU-VMTH; Tuskegee, AL, USA) with a 2-d history of inappetence and a large subcutaneous mass ventral to the left mandibular ramus, noticed 3 wk prior to presentation. The patient was not current on preventive medications or vaccines.…”
mentioning
confidence: 99%
See 1 more Smart Citation